Reproduction and recruitment of the seabob shrimp: a threatened exploitation species in southeastern of Brazil - Silva, Evelyn Raposo da; Sancinetti, Gustavo Sérgio [UNESP]; Fransozo, Adilson [UNESP]; Azevedo, Alexandre; Costa, Rogério Caetano da (Inst Pesca, 2015)
This study evaluated the reproductive period and recruitment of the threatened exploitation shrimp Xiphopenaeus kroyeri (Heller) in the southeast coast of Brazil. Monthly samples were carried out from March 2008 to February 2010 distributed in stations located inside (5, 10 and 15 m depth) and outside (25, 35 and 45 m depth) areas using a fishery boat equipped with an otter-trawl net. Water samples were taken for determination of temperature and salinity, and sediment samples for determination of texture and organic matter content. The reproductive period was determined by monthly amount (%) of females with mature gonads (ED+DE). The differences in sex ratio were tested using a Chi-square (x(2)) test. A Principal Components Analysis (PCA) was performed for an overview of the environmental variables and Redundancy Analysis (RDA) was performed to assess the relationship between abiotic factors and reproductive activity and recruitment. The size (carapace length) at the onset of sexual maturity was 10 mm and 12 mm for males and females, respectively. Reproductive females (based on gonad development) were found in all sampled months, with remarket or conspicuous peaks during winter and summer. The input of young recruits occurred one to two months after the increase of reproductive females. It was verified an optimal of temperature range for reproductive females, from 21 to 24 degrees C. These results provide subsidies that can assist making decisions about protecting priorities and in monitoring the population stocks of this important fishery resource.

Este estudo avaliou o período reprodutivo e o recrutamento do camarão ameaçado pela explotação, Xiphopenaeus kroyeri (Heller), na costa sudeste do Brasil. Amostragens mensais foram realizadas de março de 2008 a fevereiro de 2010 em estações localizadas na área interna (5, 10 e 15 m de profundidade) e na área externa (25, 35 e 45 m de profundidade) utilizando-se um barco de pesca equipado com uma rede de arrasto. Amostras de água foram coletadas para determinação da temperatura e da salinidade, e amostras de sedimento para determinação da textura e teor de matéria orgânica. O período reprodutivo foi determinado através da quantidade (%) mensal de fêmeas com gônadas maduras (ED+DE). Para verificação da proporção sexual foi utilizado o teste Chi–quadrado (χ2). Análise de Componentes Principais (PCA) foi realizada para uma análise geral das variáveis ambientais e Análise de Redundância (RDA) foi realizada para avaliar a relação entre os fatores abióticos e atividade reprodutiva e o recrutamento. O tamanho (comprimento da carapaça) da maturidade sexual foi de 10 mm e 12 mm para macho e fêmea, respectivamente. Fêmeas reprodutivas (com base no desenvolvimento das gônadas) foram encontradas em todos os meses amostrados, com os principais picos no inverno e no verão. A entrada de recrutas ocorreu 1-2 meses após o aumento de fêmeas reprodutivas. Verificou-se um intervalo ótimo de temperatura para as fêmeas reprodutivas, de 21 a 24 °C. Estes resultados fornecem subsídios que podem auxiliar na tomada de decisões sobre áreas com prioridades de proteção e no monitoramento dos estoques populacionais deste importante recurso pesqueiro.
Reprodução e recrutamento do camarão sete-barbas: uma espécie ameaçada pela explotação no sudeste do Brasil
Keywords: Xiphopenaeus kroyeri; Reproductive biology; Macae; Xiphopenaeus kroyeri; Biologia reprodutiva; Macaé